The Ethics Of Chronic Diseases And Their Management - Hayes, Bruce (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Chronic diseases – cardiovascular diseases, cancer, chronic respiratory disease and diabetes are the leading global cause of death -60% of global deaths in 2008 were from non communicable diseases, of which 80% were in low and middle income countries.